Actualización del sistema de costos de producción en la empresa E.P.I. S.A.S. (2022)
Equipos de Protección Individual S.A.S. is a company dedicated to the manufacture and wholesale marketing of products for safety at heights. The focus given to the project covers everything related to production costs in the company, in order to monitor profitability and serve as a basis for establishing or adjusting sales prices. The initial diagnosis indicated that the company, despite having a cost database, was inefficient and did not allow for monthly monitoring or easy updating of information; In addition, items were found that were not being taken into account for costing. For this reason, the main objective was to update the cost system for production orders of the company, taking into account the logistics costs and the monthly monitoring plan that allows analyzing the profitability of the products and carrying out a prior evaluation of the prices of the products. sale in the national and international market. For this, the types of manufacturing processes were studied according to the nature of each product, the personnel related to them, the time it took to manufacture a production order and the purchase of each raw material, whether national or international that includes the logistics costs of the import and its calculation method to assign it to the cost of the product. With the validation of the system, the price adjustment of products that were renting less than the 25% required by management was achieved and the cost information of 60% of the references of products with ABC classification was updated, defining a new base standard cost. Additionally, a procedure was presented for updating and monitoring the product cost system